"Red‐flag" symptom clusters in transthyretin familial amyloid polyneuropathy. Issue 1 (March 2016) - Conceição, Isabel; González‐Duarte, Alejandra; Obici, Laura; Schmidt, Hartmut H.‐J.; Simoneau, Damien; Ong, Moh‐Lim; Amass, Leslie
Abstract: Transthyretin familial amyloid polyneuropathy (TTR‐FAP) is a rare, progressive, life‐threatening, hereditary disorder caused by mutations in the transthyretin gene and characterized by extracellular deposition of transthyretin‐derived amyloid fibrils in peripheral and autonomic nerves, heart, and other organs. TTR‐FAP is frequently diagnosed late because the disease is difficult to recognize due to phenotypic heterogeneity. Based on published literature and expert opinion, symptom clusters suggesting TTR‐FAP are reviewed, and practical guidance to facilitate earlier diagnosis is provided. TTR‐FAP should be suspected if progressive peripheral sensory‐motor neuropathy is observed in combination with one or more of the following: family history of a neuropathy, autonomic dysfunction, cardiac hypertrophy, gastrointestinal problems, inexplicable weight loss, carpal tunnel syndrome, renal impairment, or ocular involvement. If TTR‐FAP is suspected, transthyretin genotyping, confirmation of amyloid in tissue biopsy, large‐ and small‐fiber assessment by nerve conduction studies and autonomic system evaluations, and cardiac testing should be performed.